2007
DOI: 10.1099/jmm.0.47353-0
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of azithromycin, newer quinolones and cephalosporins in ciprofloxacin-resistant Salmonella causing enteric fever

Abstract: The therapeutic alternatives available for use against ciprofloxacin-resistant enteric fever isolates in an endemic area are limited. The antibiotics currently available are the quinolones, thirdgeneration cephalosporins and conventional first-line drugs. In this study, the MICs of various newer drugs were determined for 31 ciprofloxacin-resistant enteric fever isolates (26 Salmonella enterica serovar Typhi and 5 S. enterica serovar Paratyphi A). MICs for ciprofloxacin, ofloxacin, gatifloxacin, levofloxacin, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 14 publications
5
32
0
2
Order By: Relevance
“…As regards, S. Typhi, these were all susceptible to ciprofloxacin and ceftriaxone. This is despite the fact that there are increasing reports of resistance to these drugs from the Indian subcontinent [20,21]. Therefore, antimicrobial activity against potential causative organisms, the severity of the cholecystitis, and the local susceptibility pattern must be taken into consideration when prescribing drugs.…”
Section: Microorganism Monomicrobialmentioning
confidence: 97%
“…As regards, S. Typhi, these were all susceptible to ciprofloxacin and ceftriaxone. This is despite the fact that there are increasing reports of resistance to these drugs from the Indian subcontinent [20,21]. Therefore, antimicrobial activity against potential causative organisms, the severity of the cholecystitis, and the local susceptibility pattern must be taken into consideration when prescribing drugs.…”
Section: Microorganism Monomicrobialmentioning
confidence: 97%
“…Indian studies have reported higher MIC90 for azithromycin in S. Typhi and S. Paratyphi A (24 μg/mL) [10,29] compared to Western studies (MIC90 8 μg/mL, MIC range 4-16 μg/mL) [30,31]. In one Indian study, taking a MIC interpretive breakpoint of >16 μg/mL, 36 (33.6%) of Salmonella isolates were azithromycin-resistant, while clinical non-response to azithromycin therapy was observed in 19 patients (both azithromycin susceptible and resistant isolates with MIC range 6-64 μg/mL, MIC90 24 μg/mL were included) [10].…”
Section: Discussionmentioning
confidence: 99%
“…Concernant la résistance à l'azithromycine, il n'existe pas encore à l'heure actuelle de concentrations critiques définies par les sociétés savantes pour cet antibiotique. Cependant, aucune souche potentiellement résistante n'a encore été documentée au CNR (CMI  8 mg/l pour 104 souches Cip S ou Cip SD isolées en 2009) ou dans la littérature, à l'exception d'une souche Cip R indienne pour laquelle la CMI de l'azithromycine était de 64 mg/l [29,37,38]. L'utilisation croissante de cet antibiotique dans cette indication étant inéluctable, il est prévisible que de telles souches résistantes émer-gent assez rapidement.…”
Section: La Résistance Aux Antibiotiques De Demainunclassified